Genetic alterations in squamous cell lung cancer associated with idiopathic pulmonary fibrosis. Issue 12 (19th February 2021) - Hata, Atsushi; Nakajima, Takahiro; Matsusaka, Keisuke; Fukuyo, Masaki; Nakayama, Manabu; Morimoto, Junichi; Ito, Yuki; Yamamoto, Takayoshi; Sakairi, Yuichi; Rahmutulla, Bahityar; Ota, Satoshi; Wada, Hironobu; et al.
Abstract: Patients with idiopathic pulmonary fibrosis (IPF) are at higher risk of developing lung cancers including squamous cell lung carcinoma (SCC), which typically carries a poor prognosis. Although the molecular basis of cancer development subsequent to IPF has not been fully investigated, we recently reported two epigenetic phenotypes characterized by frequent and infrequent DNA hypermethylation in SCC, and an association of the infrequent hypermethylation phenotype with IPF‐associated SCCs. Here, we conducted targeted exon sequencing in SCCs with and without IPF using the Human Lung Cancer Panel to investigate the genetic basis of IPF‐associated SCC. SCCs with and without IPF displayed comparable numbers of total mutations (137 ± 22 vs 131 ± 27, P = .5), nonsynonymous mutations (72 ± 14 vs 69 ± 16, P = .5), indels (3.0 ± 3.5 vs 3.0 ± 3.9, P = 1) and synonymous mutations (62 ± 9.1 vs 60 ± 12, P = .5). Signature 1 was the predominant signature in SCCs with and without IPF. SETD2 and NFE2L2 mutations were significantly associated with IPF (44% vs 13%, P = .03 for SETD2 ; 38% vs 10%, P = .04 for NFE2L2 ). MYC amplification, assessed by copy number variant analysis, was also significantly associated with IPF (18.8% vs 0%, P = .04). Mutations in TP53 and CDKN2A were observed relatively frequently in SCCs with frequent hypermethylation ( P = .02 for TP53 and P = .06 for CDKN2A ). Survival analysis revealed that the SETD2 mutation was significantly associated with worse prognosis ( P = .04). Collectively, we found frequent involvement of SETD2 and NFE2L2 mutations and MYC amplification in SCCs with IPF, and an association of a SETD2 mutation with poorer prognosis. Abstract : What's new? Patients with idiopathic pulmonary fibrosis (IPF) have an increased risk of developing lung cancers such as squamous cell carcinoma (SCC). In this study, the authors found that mutations in several cancer‐related genes were associated with SCC in IPF patients, including SETD2 and NFE2L2, as well as MYC amplification. These mutations also correlated with poor prognosis. Taken together with previous findings regarding altered DNA methylation, these results may provide new insights into the molecular basis of SCC cases arising from IPF.